Ethnobotany of spice plants among the community of emparu baru village, dedai district, sintang regency - Ege, Benediktus; Bustami, Yakobus; Wahyuni, Florentina Rahayu Esti; Nova, Monica Kristiana (STKIP Persada Khatulistiwa Sintang, 2025)
The people of Emparu Baru Village still maintain local wisdom, including the traditional use of herbs and spices as cooking spices. However, this local wisdom is still passed down orally and has not been documented in writing. This study aims to identify and document the diversity of spice plants used by the Dayak Desa community in Emparu Baru Village, Dedai District, Sintang Regency. The research employed a qualitative descriptive method with an ethnobotanical approach. The results show that the Dayak Desa people possess extensive knowledge of various types of local spice plants, including rhizomes, leaves, tubers, fruits, seeds, and others. This traditional knowledge not only plays an important role in maintaining the resilience of local species but also holds great potential to be developed as a valuable source of information for efforts to conserve plant biodiversity. Based on the ethnobotanical study of spice plants, it can be concluded that there are 42 plant species from 25 families used as spices for cooking. These spices are derived from various plant parts, including fruits, stems, seeds, flowers, leaves, young leaves, bark, rhizomes, tubers, bulbs, and shoots.